2016
DOI: 10.1371/journal.pone.0163597
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis among Youth - Testing Behaviour and Incidence of Repeat Testing in Stockholm County, Sweden 2010-2012

Abstract: BackgroundWidespread testing and screening for genital Chlamydia trachomatis is often advocated as an important method to halt the epidemic. Sweden has long tradition of opportunistic screening services. Nevertheless infections rates have continued to rise over the past two decades, despite increased access to testing and treatment services.MethodsIn this retrospective cohort study we describe the testing behavior for genital Chlamydia trachomatis among youth in Stockholm County, with a focus on repeated testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Whereas some studies reporting reinfection and retesting rates have focussed only specific patient populations (often limited to females) [ 4 , 19 , 20 ], a strength of our study was the robust sample comprising laboratory data for all males and females diagnosed with chlamydia or gonorrhoea in the region over a two-and-a-half-year period. Test locations included over 100 primary health care (general practice, youth health, student health and family planning) and sexual health clinics and all individuals had a minimum of 6 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some studies reporting reinfection and retesting rates have focussed only specific patient populations (often limited to females) [ 4 , 19 , 20 ], a strength of our study was the robust sample comprising laboratory data for all males and females diagnosed with chlamydia or gonorrhoea in the region over a two-and-a-half-year period. Test locations included over 100 primary health care (general practice, youth health, student health and family planning) and sexual health clinics and all individuals had a minimum of 6 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, repeated testing for C.trachomatis is relatively common behaviour among youth living in Stockholm County. In a recent study, we found that 42% of youth using the testing services at the Youth Health Clinics (YHC) in Stockholm re-tested for C.trachomatis during a 3 year period [ 11 ]. The repeat testers in our study tested between two to 19 times over the study period [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we found that 42% of youth using the testing services at the Youth Health Clinics (YHC) in Stockholm re-tested for C.trachomatis during a 3 year period [ 11 ]. The repeat testers in our study tested between two to 19 times over the study period [ 11 ]. Re-testing was associated with being female, a previous positive test and living in a high- or middle-income area of Stockholm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experience working in the ambulatory Gynecological consultations at Geneva University Hospital (HUG) suggests that these recommendations may need precisions. International recommendations advise CT screening for women younger than 25 years old and pregnant women [8][9][10]. Screening is also justified in older women with risk factors, such as having a new sex partner or multiple sex partners.…”
mentioning
confidence: 99%